Implementing e-learning and e-tools for care home staff supporting residents with dementia and challenging behaviour: A process evaluation of the ResCare study using normalisation process theory - Keenan, Julia (Dementia (London), 2018)
Dementia-related symptoms, sometimes termed challenging or distressing behaviour, can give rise to significant distress in care homes. Individualised formulation-led interventions show promise in reducing these behaviours. ResCare, a cluster randomised controlled trial in England, tested an online individualised intervention, comprising e-learning and decision support e-tools, designed to enable staff to better support residents with such symptoms. Normalisation process theory was used to understand the implementation processes. We analysed contextual process data for all 27 ‘intervention’ care homes and identified three implementation mechanisms. These were examined for four illustrative case study homes. Seven qualitative interviews with care home staff and one interview with two research therapists informed this understanding. The main barrier to implementation was difficulty in conveying a sustained understanding of the value of individually tailored interventions. Emphasis was placed on training rather than practice change. Implementation seemed easier in smaller homes and in those with flexible managerial styles where transfer of knowledge and skill might have been easier to achieve. Take up of e-learning and e-tools proved hard. There may be a need to continually promote ‘buy-in’ of the potential benefits of individualised formulation-led interventions, and this would have to be congruent with other priorities. Interventions within care homes need to consider organisational readiness, capacity for innovation and ongoing appraisal and adjustment to maintain changes in practice.